Control de Inventarios Mercaderías en la Gestión Administrativa Financiera del Comisariato San Rafael, del cantón Caluma, Provincia Bolívar, año 2016 - Espín Pozo, Marcia Kimena (2018)
The present research project is carried out so that the San Rafael Commissariat of the city of Caluma has an adequate control of merchandise inventories, so that it helps to administer the resources, also obtain a financial information and that the existing merchandise is the real one. The present investigation is used as a support to identify the shortcomings that the company is going through, its important problem is that they do not have an adequate control of merchandise inventories, because they have an inventory control system but they do not use it. they must give it, the merchandise is entered in an incorrect way. The main objective of this research project is that we must provide alternative solutions for the control of merchandise inventories, so that the company's resources can be properly managed and the Manager can make decisions that contribute to the economic development of his company. The methodology we used for the development of this research was the inductive, deductive, synthesis and analysis methods and instruments for obtaining information, the manager was interviewed, the workers survey and direct observation, thus showing the analysis and interpretation From the results. In conclusion it is established that with an adequate control of inventories in San Rafael Commissariat, the company will be able to distribute its products in a correct and suitable way and each product has its corresponding characteristics, the existing quantities are real, for the exposed above, it is recommended that personnel be trained so that they know the importance of inventory control merchandise, so they can take a proper financial management and that the utilities are real.